A combined GCMC and LBM simulation method for CH4 capture in Cu-BTC particle adsorption bed. (November 2017) - Wang, H.; Qu, Z.G.; Zhou, L.
Abstract: Two-dimensional Lattice Boltzmann Method (LBM) combined with grand canonical Monte Carlo (GCMC) approach is proposed to investigate the heat and mass transfer of methane (CH4 ) adsorption in Cu-BTC particle adsorption bed. In interfacial boundary, saturation adsorption capacities are obtained by GCMC method to replace empirical values. The diffusion and adsorption heat in particle interior are fully considered. Langmuir-Freundlich model and linear fitting formula are used to calculate the saturation adsorption capacities in Langmuir adsorption kinetics model and the adsorption heat in heat transfer in LBM model at mesoscopic level, respectively. At micro-scale level, GCMC method is used to obtain parameters of Langmuir-Freundlich and linear fitting formula. The effects of porosity and particle size on CH4 adsorption are discussed. Results show that the time for the saturation adsorption decreases with an increase in porosity and increases with increased particle size. In fluid region and particle interior, temperature peak decreases with increasing porosity and particle size. Nonuniformity of temperature exists both in fluid region and solid particles. The adsorption properties in Cu-BTC adsorption bed, such as the relation between external and internal heat and mass transfer, is predicted intuitively by GCMC and LBM combined simulation method.